BIOATIVIDADE DE VIDROS NO SISTEMA 2Na2O.1CaO.3SiO2-P2O5 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
Progress in medicine has led to an increase in life expectancy of the world population. On the other hand, the properties of certain tissues and organs that compose the human body continues to follow the aging process. Faced with this challenge, biomaterial are developed with new technologies for bone substitutes. In this study we investigated the bioactivity of the glasses system 2Na2O.1CaO.3SiO2 with 0, 3 and 6% P2O5 in weight. The bioactivity was studied by immersion in simulated body fluid solution. Heat treatments were also performed in order to study the bioactivity of these glass-ceramics. Differential scanning calorimetry was performed to determine the glass transition temperatures for the glasses. Through Fourier transform infrared spectroscopy analysis was used to verify the bioactivity. The hardness and elastic modulus of the glasses were determined by the instrumented nanoindentation. X-ray diffraction confirmed the crystalline phases present in the glass ceramic samples. It was observed the formation of a hydroxycarbonate apatite layer after 21 days in samples of glass 2Na2O.1CaO.3SiO2 with 0, 3 and 6% P2O5 in weight. The best condition for the growth of hydroxycarbonate apatite layer in the glass-ceramics was the 2Na2O.1CaO.3SiO2 + 3% P2O5 that received heat treatment of 15 hours at 560° C. We observed the growth of the hydroxycabonate apatite layer after 7 days, and the glass-ceramic 2Na2O.1CaO.3SiO2+6% P2O5 who received heat treatment of 15 hours at 560° C the hydroxycabonate apatite layer was observed after 14 days in vitro novel. It was observed that cristalyzation is reduced with increase P concentration. At glass-ceramics with 6%wt of P2O5 the crystals are richer in Ca than in the stoichiometric glass matrix. In opposition, for 1Na2O2NaO3SiO2 glass-ceramics, the crystals are richer in Na.x
Keywords: vidros bioativos; hidroxicarbonato de apatita; vitrocerâmicas; bioactive glasses; hydroxycarbonate apatite; vitroceramics; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA